Vjerska problematika u pravaškom tjedniku Hervatska 1871. godine (Povijesni prilozi (Historical Contributions), 2024)
Based on scholarly literature and periodicals, primarily articles published in the Party of Rights’ weekly Hervatska, this paper offers an overview of the opinions expressed by Ante Starčević, Eugen Kvaternik, the young associates in the editorial office, and the weekly’s correspondents on various religious and church-related matters. The weekly engaged in discussions influenced by domestic and European political events, addressing the abolition of the Papal State in 1870, the secular authority of the Pope, and the appointment of bishops in Croatia. During this time, there was intense criticism directed towards Bishop Strossmayer for his statements regarding Protestants and the dogma of papal infallibility, which had been confirmed during the First Vatican Council. These discussions marked the beginning of a fierce conflict that would escalate in the subsequent months, particularly during the May elections for the Croatian Parliament in 1871 and thereafter. The conflict emerged between the supporters of the Party of Rights and the Catholic clergy who aligned themselves with Strossmayer’s National Party. The First General Assembly of Croatian Teachers provided the collaborators of Hervatska with an opportunity to express their support for the secularization of education. Additionally, debates on the Paris Commune brought to light differences between the deeply religious Kvaternik and his young collaborators in the editorial office of Hervatska regarding social issues, particularly the notion of religion and its role in the society.